UNIVERSAL ZULU NATION AS THE BLACK COUNTER-HEGEMONY ON AFRIKA BAMBAATAA’S SONG “RENEGADES OF FUNK” - NURCAHYO, VICTORIO JERRY (Jurnal Ilmiah Mahasiswa FIB, 2013)
Culture reflects the character of a nation. In the culture also contains historical values ​​of a nation, and cultures can come through a lot of things and one of them is through music or lyrics. The author conducted research on counter-hegemony by the Zulu Nation presented by Afrika Bambaataa through the Renegades of Funk lyrics. There are two problems to be solved in the study, namely: (1) Why does Afrika Bambaataa create Zulu Nation as counter-hegemony in the American Hip-Hop movement, (2) How can "Renegades of Funk" lyrics affect a person's outlook and lifestyle. This study uses the counter-hegemony theory in relation which the author analyzes the lyrics of the title, as well as a cultural studies approach to the phenomenon of Hip-Hop and Zulu Nation in America. The study results revealed that Gramsci's theory of hegemony is closely associated with cultural studies. Wherein, the hegemony hands in hand with counter-hegemony in shaping a nation's character traits. Hegemony here is mirrored by the American system of government and also the hegemony of Hip-Hop itself, that's what made the two great camps between traditional intellectuals and organic intellectuals. Government system as a representative of the traditional intellectual while Afrika Bambaataa and the Zulu Nation is representative of the organic intellectual. The analysis of the rivalry between the hegemony of the Zulu Nation and the song "Renegades of Funk" as a counter-hegemony product from author’s study analysis.The author suggests next students majoring in English Department to learn more about the Hip-Hop cultural studies in America as well as the hegemony that the birth of a cultural form. Then, the authors also suggest further research to investigate more about the history of Hip-Hop music by a semiotic approach to cinematography studies in the video clip "Renegades of Funk" which is covered by the band Rage Against the Machine. Keywords: zulu nation, counter-hegemony, afrika bambaataa, renegades of funk.